If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6v = -3(-15v + -17) Reorder the terms: -6v = -3(-17 + -15v) -6v = (-17 * -3 + -15v * -3) -6v = (51 + 45v) Solving -6v = 51 + 45v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-45v' to each side of the equation. -6v + -45v = 51 + 45v + -45v Combine like terms: -6v + -45v = -51v -51v = 51 + 45v + -45v Combine like terms: 45v + -45v = 0 -51v = 51 + 0 -51v = 51 Divide each side by '-51'. v = -1 Simplifying v = -1
| -3(9+11w)=-(12+18w) | | 3.54x+1=12.5216+x | | x^20-2x^10+1=0 | | x^30-2x^10+1=0 | | -2(-19+16)=3(16z+20)+18 | | X^30+x^10+1=0 | | 4d=12-6(-2d+10) | | 2x-3/4=0 | | 5(-7g+15)=-5-15g | | 15+19y+19=-19y-3(-15y+19) | | f(x)=2x-3/4=0 | | t^4-t^2-1=0 | | 5j=5(6j-10) | | 3(2)+y=12 | | 3x/5-6=9 | | 3(6)+y=12 | | x+11=2x-1 | | -7+6(-4q+19)=20-3-19q | | 3(4)+y=12 | | 8(x-4)+9-3(x+5)+38=0 | | 29x+5=30x+1 | | 8x-7+3-x=14-4x | | 99=-3x | | 8.3u+19.72-18.2u=-19.88-14.4u | | x*x+x-42=0 | | 8x-7+3-x=14+4x | | 6f+11.89=1.9f | | -4.41-11.9k=14.38-10.4k+8.96 | | 8x-7-3-x=14+4x | | -k(x-1)+2kx=1 | | 18.7-15.1b=-17.4b-19.02 | | x/.010 |